Ideal Teacher According to Students of German Language SMAN 1 Batu - Wida Ainur Rofiqoh (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2019)
This study aims to determine the criteria of the ideal teacher according to students in SMA Negeri 1 Batu. This study used a descriptive quantitative approach with a survey being the method. The data were obtained from questionnaires distributed to 121 respondents comprising all of the German students from 10th to 12th graders and the teacher. The result obtained was in the form of opinions regarding the notion of an ideal teacher. The result showed that the criteria of ideal teacher include material and lesson plan, preparedness prior to teaching, being familiar with students, understanding student capabilities, attentive, motivating, understandable explanation of materials, creative, implementing attractive learning method and media, responsive, tech-savvy, appreciative, patience, having sense of humor, assertive, discipline, objective, responsible, good role model for students. However, a number of criteria were not in accordance with the statements of the experts, namely the teacher does not give excessive assignments, yet always gives homework.